General Drinking Motives and Alcohol Consumption across Three Contexts: Drinking Games, Tailgating, and in Stadium. (1st June 2022) - Hoyer, Dennis; Corriea, Christopher J.
Abstract: Background: Alcohol consumption across specific events and contexts has been identified as an important area of research related to college student drinking. Contexts associated with increased risk for negative outcomes include drinking games and football games at large universities. Additionally, drinking motives have been linked to increased consumption and consequences. The current study aimed to assess the role of general drinking motives across a variety of specific contexts. Methods: Self-report measures related to general alcohol consumption, general drinking motives, and context-specific consumption were completed by a final sample of 553 predominantly female and white students. Three sets of hierarchical regression analyses were conducted to measure relations between drinking motives and the number of drinks consumed in the contexts of drinking games, tailgating outside of the stadium prior to home football games, and while inside the football stadium during home games, after accounting for the number of times participating in each respective context. Results: Concerning tailgates, conformity and enhancement motives were positively related to the number of drinks consumed. Conformity motives were associated with greater consumption in the contexts of drinking games and in-stadium drinking. Social motives were inversely related to the number of drinks consumed in-stadium. Conclusion: Different general drinking motives may contribute to individuals' alcohol consumption across specific contexts. While conformity motives are not traditionally viewed as a unique risk factor for problematic use, the relation between conformity motives and consumption while playing drinking games and within the stadium provides novel results about their potential role in alcohol-related outcomes.